Reasons for opposition to posthumous reproduction and prior consent: attitudes of Jewish men during the ongoing armed conflict - Bella Savitsky (Israel Journal of Health Policy Research)
Abstract Following the outbreak of armed conflict in Israel on October 7, 2023, a new directive permits both the spouse and parents of a deceased individual to initiate sperm extraction without the need for a court order or prior consent. A previous study revealed that nearly 37% of men in relationships opposed PSR at their partner’s request, and half of the men whose parents are alive opposed PSR at their parents’ request. The current study aims to explore the reasons behind this opposition and to understand the underlying attitudes of those who object to PSR. The study population consists of 600 Jewish men aged 18–49, with data collected between February and March 2024 through a questionnaire. Main objections for PSR following parental or partner`s request centered on the perceived “unethical nature of planned orphanhood”. The level of religiosity was significantly associated with this theme: the proportion of men who cited this reason for opposing PSR following a partner’s request was 33.3% among secular men, 42.9% among traditional men, and 70.4% among religious men (p =.007). The most common reason for opposing the collection of prior consent before army enlistment was the belief that “Eighteen-year-old conscripts are just children who don’t understand anything”; “The moment of enlistment is not the right time to ask such a complex question” and “It is unethical to invest in any process that would create planned orphanhood”. The study emphasizes the need for prior consent and highlights the need for culturally sensitive and ethically informed PSR policies.